Histologic and Immunohistochemical Characterization of Pheochromocytomas in 20 Clouded Leopards (Neofelis nebulosa). (March 2017) - Corner, S.; Walsh, T.; Padilla, L.; MacNeill, A.; Wallig, M.; Kiupel, M.; Terio, K.
Clouded leopards in North American zoological institutions have a high frequency of pheochromocytomas and were identified in 32 of 70 (45%) animals necropsied. Archival sections of adrenal gland from 20 adult clouded leopards with unilateral or bilateral pheochromocytomas collected between 1984 and 2011 were examined by light microscopy and immunohistochemistry, and case demographics were reviewed. Affected leopards were older than 10 years of age (mean, 16 years; range, 11–19 years), and males were overrepresented (12 males, 8 females). Pedigree analysis yielded no evidence for heritability. Five clouded leopards had bilateral neoplasms. Pheochromocytoma was the cause of death due to invasion of the caudal vena cava and fatal hemorrhage in 4 cases. Most pheochromocytomas were well-demarcated, nodular, and expansile masses composed of cords and packets of neoplastic polygonal cells. Five pheochromocytomas had vascular invasion, of which 4 resulted in hemorrhage that was the cause of death. One of the latter pheochromocytomas also had pulmonary metastasis. Ultrastructurally, neoplastic cells had cytoplasmic structures consistent with both norepinephrine- and epinephrine-containing granules. In all cases, neoplasms were immunohistochemically positive for chromogranin A, protein gene product 9.5, and synaptophysin. A subset of neoplasms evaluated by tissue microarray were positive for met-enkephalin and β-endorphin and negative for melan-A. Histologically, 7 of 20 (35%) clouded leopards with pheochromocytomas had retinal detachment, retinal degeneration, or intramyocardial muscular arteriosclerosis, suggestive of hypertension. Pheochromocytomas can cause mortality and may be a source of clinically significant hypertension in clouded leopards. These neoplasms share similar histologic, immunohistochemical, and ultrastructural characteristics with those of other species.